Local tunability in a multi-port SQUID by an injection current. (1st November 2021) - Xu, Zuyu; Tian, Wanghao; Chen, Shixian; Yue, Wencheng; Du, Hongmei; Li, Dingding; Wei, Zihan; Lyu, Yang-Yang; Sun, Hancong; Wang, Yong-Lei; Sun, Guozhu; Chen, Jian; et al.
Abstract: The tunability in Josephson junctions is foundational to the superconducting classical and quantum applications. Here, we demonstrate the local manipulation of supercurrent realized in a superconducting quantum interference device (SQUID) with two Nb/TiO x /Nb Josephson junctions that is biased at the TiO x layer. Our measurements indicate that the multi-port device allows for an easy and in situ tunability of the supercurrent. The control mechanism can be finely explained by simple yet valid theoretical methods, which take an effective electronic temperature across the SQUID and the self inductive magnetic flux into account. Furthermore, we show that the phase difference and kinetic inductance of this device can be tuned locally via the injection current. Thus, the device provides perspective for several superconducting electronics such as tunable superconducting circuits, sensitive magnetometry, and fast digital elements.